EFEKTIVITAS WAYANG SYADAT SEBAGAI MEDIA DAKWAH ISLAM DI DUSUN KEMBANGBAU PURWOKERTO NGIMBANG LAMONGAN - Khozainul Ulum; Moh. Ah. Subhan ZA (Akademika, 2019)
Wayang (puppet-shadow play) syadat is a new puppet creation that is similar to the so-called wayang suluh as a result of the modification and acculturation conducted by Walisongo. Like wayang suluh, wayang syadat is also used as a means of preaching Islamic values and teachings to the community, especially the people in Kembangbau, Purwokerto, Ngimbang, Lamongan and so on. Although the standard of the wayang syadat is the same as the one of the wayang in general, there are additional performances to the show, namely the religious sermon and prayers at the beginning of the performance. The effectiveness of the wayang syadat performance as a means of preaching Islamic teachings to the Kembangbau people because they like the tradition of "wayang". On this stand, the Islamic values inserted in any wayang syadat performance could be accepted without any coercion. Finally, they consciously apply and practice the Islamic values or teachings in their everyday lives.